The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11064-011-0669-x
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with a Novel Metallopharmaceutical NO Donor in Anesthetized Rats Subjected to Brain Ischemia/Reperfusion

Abstract: Rut-bpy is a novel nitrosyl-ruthenium complex releasing NO into the vascular system. We evaluated the effect of Rut-bpy (100 mg/kg) on a rat model of brain stroke. Forty rats were assigned to four groups (Saline solution [SS], Rut-bpy, SS+ischemia-reperfusion [SS+I/R] and Rut-bpy+ischemia-reperfusion [Rut-bpy+I/R]) with their mean arterial pressure (MAP) continuously monitored. The groups were submitted (SS+I/R and Rut-bpy+I/R) or not (SS and Rut-bpy) to incomplete global brain ischemia by occlusion of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…There is a growing body of evidence that synthetic NO donors have efficacy in animal models of cerebral ischemia. For example, intraperitoneal injection of NO donor Rut-bpy prior to ischemia/reperfusion reduced brain infarct zone and improved viability of hippocampal neurons [7]. Another NO donor, NOC-18, protected brain mitochondria against ischemia-induced dysfunction [2].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that synthetic NO donors have efficacy in animal models of cerebral ischemia. For example, intraperitoneal injection of NO donor Rut-bpy prior to ischemia/reperfusion reduced brain infarct zone and improved viability of hippocampal neurons [7]. Another NO donor, NOC-18, protected brain mitochondria against ischemia-induced dysfunction [2].…”
Section: Discussionmentioning
confidence: 99%
“…NFKB activated in podocytes. NFkB activation and NO production by NOSi are known to lead to cell damage, as shown in experimental rat model 8 , and also promote glomerulonephritis 22 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Currently, a metallopharmaceutical named Rut-bpy (Cis-[Ru(bpy) 2 (SO3)(NO)]PF 6 ) can release NO in vitro and in vivo, as well as it can reduce inflammatory processes through NF-kB inhibition 7,8 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…This may suggest a beneficial role of nNOS during early stages of epileptogenesis in contrast to its proconvulsive role during acute seizures onset (SE). It has been shown that a transient increase in nNOS, following insult to the brain, protect neurons by S-nitrosylation of NR2B subunit of NMDAR to control excessive calcium influx (Gidday et al, 1999; Gonzale-Zulueta et al, 2000; Campelo et al, 2012). Since we did not observe expected modifications in early epileptogenesis by inhibiting nNOS with L-NPA, we focused our investigation on the role of iNOS in epileptogenesis.…”
Section: Inducible Nos Inhibitor and Epileptogenesismentioning
confidence: 99%
“…This may suggest a beneficial role of nNOS during the early stages of epileptogenesis in contrast to its proconvulsive role during acute seizure onset (i.e., SE). It has been shown that a transient increase in nNOS, following insult to the brain, protects neurons by S-nitrosylation of the NR2B subunit of NMDAR to control excessive calcium influx (Campelo et al, 2012;Gidday et al, 1999;Gonzalez-Zulueta et al, 2000).…”
Section: N Os I Nh I Bi Tor a N D E P I Le P Toge Ne Si Smentioning
confidence: 99%